Penerapan Metode Multi-Objective Optimization on the Basis of Ratio Analysis (MOORA) dengan Pembobotan Rank Order Centroid (ROC) Dalam Sistem Pendukung Keputusan Pemilihan Guru Terbaik - Rahma Yuni Simanullang; Mesran Mesran (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
A decision support system (DSS) is a system that can solve problems that occur in ranking quickly and can find out the highest to lowest values ??in a selection. At this writing, it is a case study that can be solved using a decision support system, where the problem faced at SDN 153030 Kedai Gedai 1 Barus District is how to choose the best teacher in the school and to make a selection you have to use manual methods and the assessment process takes a long time to get results. Therefore a decision support system is created that can assist the assessment process. This decision support system is carried out using the MOORA and ROC methods where this method is used for testing which aims to determine the accuracy of the values ??obtained by the system, sensitivity trials are given to criteria weight values ??and modification trials that aim to find out how many criteria can be added and each criterion has its own weight value and the alternatives will be ranked. After ranking, the results obtained from the calculation of the MOORA and ROC methods are Rama Hutagalung AMa.Pd (A3) with a value of 0.370. These results can facilitate the selection team in making decisions and being selected as the best teacher at SDN 153030 Kedai Gedang 1 Barus District